2018
DOI: 10.1039/c7ob02040f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced structural diversity in terpenoid biosynthesis: enzymes, substrates and cofactors

Abstract: The enormous diversity of terpenes found in nature is generated by enzymes known as terpene synthases, or cyclases. Some are also known for their ability to convert a single substrate into multiple products. This review comprises monoterpene and sesquiterpene synthases that are multiproduct in nature along with the regulation factors that can alter the product specificity of multiproduct terpene synthases without genetic mutations. Variations in specific assay conditions with focus on shifts in product specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 125 publications
1
50
0
Order By: Relevance
“…Natural class I terpene synthases precisely pre-orient their acyclic diphosphate substrates in their active site pockets in a reaction-ready conformation. Then, the complex reaction cascade is initiated by cleaving off the diphosphate group from the pre-oriented substrate molecule, a pH-dependent [4] process that requires divalent metal ions as cofactor [28,29]. It has been shown that this ionization step of the allylic diphosphate is the rate-limiting step in a class I terpene synthetase catalysis [30].…”
Section: Protonation-dependent Diphosphate Cleavagementioning
confidence: 99%
See 1 more Smart Citation
“…Natural class I terpene synthases precisely pre-orient their acyclic diphosphate substrates in their active site pockets in a reaction-ready conformation. Then, the complex reaction cascade is initiated by cleaving off the diphosphate group from the pre-oriented substrate molecule, a pH-dependent [4] process that requires divalent metal ions as cofactor [28,29]. It has been shown that this ionization step of the allylic diphosphate is the rate-limiting step in a class I terpene synthetase catalysis [30].…”
Section: Protonation-dependent Diphosphate Cleavagementioning
confidence: 99%
“…We also introduce a graph database to integrate the simulation results with experimental biological evidence for the selected predicted sesquiterpenes biosynthesis.Processes 2019, 7, 240 2 of 18 "biogenetic isoprene rule" according to which terpenes are the result of concatenating isoprene units in a "head-to-tail" fashion to form chains, from which then rings are formed. Prenyltransferases condense IPP and DMAPP to geranyl pyrophosphate (GPP), farnesyl pyrophosphate (FPP), and geranylgeranyl pyrophosphate (GGPP) as the entry points to the world of monoterpenes (C 10 ), sesquiterpenes (C 15 ), and diterpenes(C 20 ) [4]. FPP and GGPP can then be condensed further to form squalene (C 30 ) and even largermolecules [5].These intermediates are substrates for a class of enzymes known collectively as terpene synthases (TPSs) to produce a wide variety of compounds.…”
mentioning
confidence: 99%
“…Natural class I terpene synthetases precisely pre-orient their acyclic diphosphate substrates in their active-site pockets in a reaction ready conformation. The complex reaction cascade is than initiated by cleaving off the diphosphate group from the pre-oriented substrate molecule, a pH-dependent [4] process that requires divalent metal ions as co-factor [25,26]. It has been shown, that this ionization step of the allylic diphosphate is the rate-limiting step in class I terpene synthetase catalysis [27].…”
Section: Protonation-dependent Diphosphate Cleavagementioning
confidence: 99%
“…Leopold Ružička [3] formulated the "biogenetic isoprene rule" according to which terpenes are the result of concatenating isoprene units in a "head-to-tail" fashion to form chains, from which then rings are formed. Prenyltransferases condense IPP and DMAPP to geranyl pyrophosphate (GPP), farnesyl pyrophosphate (FPP), and geranylgeranyl pyrophosphate (GGPP) as the entry points to the world of monoterpenes (C 10 ), sesquiterpenes (C 15 ), and diterpenes (C 20 ) [4]. FPP and GGPP can then be condensed further to form squalene (C 30 ) and even larger molecules [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation